Effects of BMP9 and pulsed electromagnetic fields on the proliferation and osteogenic differentiation of human periodontal ligament stem cells. Issue 1 (11th November 2016) - Wang, Tingting; Wang, Pei; Cao, Zhizhong; Wang, Xingxing; Wang, Dalin; Shen, Yaxian; Jing, Da; Luo, Erping; Tang, Weizhong
Abstract : Periodontal ligament stem cells (PDLSCs) have been confirmed to have self‐renewal capacity and multidifferentiation potential and are good candidates for periodontal tissue regeneration. Pulsed electromagnetic field (PEMF) has been demonstrated to promote osteogenesis in non‐union fractures, partly by regulating mesenchymal stem cells or osteoblast activity. However, there is no report about the osteo‐inductive effect of PEMF stimulation on human PDLSCs (hPDLSCs). Thus, we tested the hypothesis that PEMF biophysical stimulation alone has an influence on the proliferation and osteogenic differentiation of hPDLSCs. To detect the osteo‐inductive potential of bone morphogenetic protein (BMP9), we transfected the STRO‐1 + /CD146 + hPDLCSs with BMP9‐expressing recombinant adenoviruses. We examined the proliferation and osteogenic differentiation of hPDLSCs treated with either PEMF (15 Hz, 1 h daily, different intensities), or BMP9, or both stimuli. Cell counting kit‐8 (CCK‐8) assay showed that PEMF of different intensities had no effect on the proliferation of hPDLSCs and did not enhance the proliferative capability of BMP9‐transfected cells. Quantitative real‐time polymerase chain reaction (qRT‐PCR) and Western blotting showed that the combination of both PEMFs (1.8 or 2.4 mT) and BMP9 stimulation had a synergistic effect on early and intermediate osteogenic genes and protein expressions of runt‐related transcription factor 2, alkaline phosphatase, osteopontin, and late mineralized extracellular matrix formation in hPDLSCs. Bioelectromagnetics. 38:63–77, 2017. © 2016 Wiley Periodicals, Inc.